CONSUMER RESPONSE ON MARKETING MIX OF ALOE VERA GREEN PRODUCTS IN PONTIANAK WEST KALIMANTAN, INDONESIA: CONSUMER RESPONSE ON MARKETING MIX OF ALOE VERA GREEN PRODUCTS IN PONTIANAK WEST KALIMANTAN, INDONESIA - Maswadi; Darsono; Slamet Hartono; Kusnandar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
Abstract: Green products or which are also often referred to as environmental friendly products that are complex enough to be defined. Green products made from aloe vera produced by a small company of processed aloe vera, which has been developed in Pontianak, West Kalimantan Indonesia experienced excellent growth in the development of refined products are made. Initially only aloe vera drinks are produced but it's been producing aloe vera into jelly, tea, dodol, chocolates and crackers. The purpose of this study is to analyze consumer response on marketing mix of green products processed aloe vera in Pontianak City. The research method in this study is a survey method. Sample of consumers used incidental sampling technique. The analytical tool used is conjoint analysis with the matrix between 5-P i.e. production / product (P), price (P), Place (P), promotion (P), people or 5-P with agro-industry customer satisfaction with the product. The results showed that marketing mix which has influence on green products processed aloe vera, in the sequence is price (19.93%), place (19.16%), product (18.57%), packaging (16.31%), performance (15.83%) and promotion (10.18%). Keywords: aloe vera; consumer response; green products; marketing mix; conjoint analyz